(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
The main thesis in the paper is that the harmonization of environmental legislation will have an impact on the labor market. In practice, new green jobs are emerging and the transformation of existing ones is happening. It can be said that the transition to a greener economy will create new jobs across a range of sectors, but others may face difficulties as certain industries and occupations decline. As the transition to environmentally friendly jobs will at first increase the unemployment, the unemployment insurance plays an important role here in terms of developing the skills that unemployed people need, i.e. job training, to be able to return to work in an environmentally sustainable economy. There are reasons for normative intervention in the system of unemployment protection, which require building an eco-strategic skill development framework. The main objective to be achieved by eco-intervention in the unemployment insurance system is to change the structure of the workforce, i.e. improve the bond between the demand and the supply of skills to the labor market, which is also highlighted in the National Employment Strategy of the Republic of Macedonia 2016-2020. The paper will answer the question of what is the role of the social dialogue and the role of the Employment Agency whose activities can be crucial to the success of such a strategy.